Methodological foundations for physical rehabilitation of patients on intermittent asthma. - Grigus I.M; Prusik Krzysztof; Prusik Katarzyna; Hagner-Derengowska Magdalena (Kharkov National Pedagogical University, 2011)
The aim was to improve the physical rehabilitation of patients with intermittent bronchial asthma exacerbation by applying the pathogenetic modes of physical activity and a range of physical therapeutic factors. A total of 70 patients with intermittent asthma in the acute stage. In the hospital carried out a specific program of physical rehabilitation, including the modified methods of therapeutic physical culture and physiotherapy facilities. The use of physical rehabilitation resulted in a reduction of assault period of the disease, significantly improved the physical performance of patients. In all cases of physical rehabilitation program achieved full control of the disease, significantly improves the quality of life of patients, did not occur in the treatment of patients with only medicines.